Sosialisasi pertolongan pertama pada kecelakaan sehari - hari - Mutmainnah Mutmainnah; Sarifah Sarifah; Etno Etno (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of this activity is how to do first aid for accidents that are often experienced everyday. Students as members of the community, especially because IKOR FIK UNM students have the basis of anatomy and human physiology. So that the provision of this material is expected to make them understand and be able to do first aid and know what not to do. The purpose of this first aid is to save lives or prevent death, prevent more severe disabilities, prevent infection, maintain the power of the victim until further help arrives and reduce pain and fear.Some of the daily accidents discussed are fainting, epilepsy, nosebleeds, leg cramps, bruises, sprains, wounds, burns, broken bones and insect bite. The implementation of this activity was conducted at FIK UNM.